Propaganda objectives and instruments as an element of foreign policy : case of Russian-Ukranian conflict - Diukova, Anfisa; Lisa, Aleš, 1956-; Vymětal, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
A comparative qualitative analysis of propaganda as a tool of Russian and Ukrainian foreign policy was conducted, utilizing data gathered from February 24, 2022, to February 24, 2024. The objective of this study is to characterize the narratives employed by both nations within the sphere of war propaganda and to ascertain the methodologies each employs to influence public opinion. The thesis elucidates the specific imagery Russia and Ukraine seek to promulgate, the underlying rationales, and the instrumentalities they employ for such purposes.
Vedoucí práce: Aleš Lisa
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses